Development of thulium-doped and co-doped fiber lasers for 1.9 micron region operation / Norazlina Saidin - Norazlina, Saidin (2015)
1.9 μm fiber lasers offer numerous applications in the area of spectroscopy, military and medical field. Thulium doped fiber has been used in order to realize laser applications in this region. Various methods have been implemented to achieve high output power as well as low threshold pump power for the laser’s applications. Other than being used for continuous wave operation, pulse lasers are also important in various fields of applications including high-precision material processing, biomedicine and ranging. This thesis thoroughly describes the development of 1.9 μm fiber lasers based on thulium doped and co-doped fibers as the gain medium. Two different co-doped fibers; ytterbium-thulium co-doped fiber (YTDF) and thulium-bismuth codoped fiber (TBF) is investigated. A lasing action was successfully obtained at the 1901.6 nm wavelength using two YTDF samples with different Ytterbium and Thulium concentration based on the cladding pumping technique. Higher ytterbium to thulium concentration ratio exhibits better lasing efficiency and threshold pump power which utilizes a linear configuration device pumped by a 931 nm pumping wavelength. The enhancement of lasing performance has been identified in TBF compared to YTDF and commercial thulium doped fiber (TDF). By using three TBF samples (TB1, TB2, TB3), TB2 which contains the highest amount of active bismuth and thulium concentrations, exhibit the best lasing efficiency of 42.2% at a threshold pump power of 92 mW by employing a 0.4 m long fiber. The energy transfer process can be optimized by adjusting the dopants compositions thus increasing the efficiency of the stepwise energy transfer. An all-fiber 1.9 μm Q-switched laser has been successfully constructed using commercial TDF and TBF as the gain medium in a ring cavity configuration. Reliable self-starting Q-switched lasers based on graphene saturable absorber (GSA) and multiwalled carbon nanotube saturable absorber (MWCNT-SA) were observed. Both of the GSA and MWCNT-SA were fabricated in-house using new preparation method. The best Q-switched laser was generated by a 1.5 m long TB2 in conjunction with the MWCNT-SA. A wide pump power range of 500 mW to 800 mW with the highest repetition rate and lowest pulse duration of 61.99 kHz and 4.0 μs, respectively have been achieved using a 1552 nm pumping wavelength. Besides that, an all-fiber ring cavity configuration is significant for the compatibility of silica host with standard optical components. Compared to the other 2 μm Q-switched fiber laser, the proposed laser configuration is simpler and more compact.